Impaired Glycine Receptor Trafficking in Neurological Diseases - Schaefer, Natascha; Roemer, Vera; Janzen, Dieter; Villmann, Carmen (Frontiers in Molecular Neuroscience, 2018)
Ionotropic glycine receptors enable fast synaptic neurotransmission in the adult spinal cord and brainstem. The inhibitory glycine receptor is a transmembrane glycine-gated chloride channel. The immature glycine receptor protein undergoes various processing steps e.g. folding, assembly, and maturation while traveling from the endoplasmic reticulum to and through the Golgi apparatus, where posttranslational modifications e.g. glycosylation occur. The mature receptors are forward transported via microtubules to the cellular surface and inserted into neuronal membranes followed by synaptic clustering. The normal life cycle of a receptor protein includes further processes like internalization, recycling, and degradation. Defects in glycine receptor life cycle, e.g. impaired protein maturation and degradation have been demonstrated to underlie pathological mechanisms of various neurological diseases. The neurological disorder startle disease is caused by glycinergic dysfunction mainly due to missense mutations in genes encoding glycine receptor subunits (GLRA1 and GLRB). In vitro studies have shown that most recessive forms of startle disease are associated with impaired receptor biogenesis. Another neurological disease with a phenotype similar to startle disease is a special form of stiff-person syndrome, which is most probably due to the development of glycine receptor autoantibodies. Binding of glycine receptor autoantibodies leads to enhanced receptor internalization. Here we focus on the normal life cycle of glycine receptors concentrating on assembly and maturation, receptor trafficking, postsynaptic integration and clustering, and glycine receptor internalization/recycling/degradation. Furthermore, this review highlights findings on impairment of these processes under disease conditions such as disturbed neuronal ER-Golgi trafficking as the major pathomechanism for recessive forms of human startle disease. In stiff-person syndrome, enhanced receptor internalization upon autoantibody binding to the glycine receptor has been shown to underlie the human pathology. In addition, we discuss how the existing mouse models of startle disease increased our current knowledge of glycine receptor trafficking routes and function. This review further illuminates receptor trafficking of glycine receptor variants originally identified in startle disease patients and explains changes in the life cycle of glycine receptors in patients with stiff-person syndrome with respect to structural and functional consequences at the receptor level.